"Indianize the 'Q' ra '": a new knowledge policy - Sanjinés, Javier (2016)
The presence in Bolivia of a radical "katarismo" promoted by recent indigenist movements, obliges a rethinking of the politics of criollo-mestizo knowledge. In this sense, the article locates the proposal to indianize the q' ara (the mestizos) as a reverse pedagogy from which the radical katarist ideologue Felipe Quispe, alias "Mallku': questions from below the mestizaje that dominant groups have promulgated since the beginning of the century.